Advances in understanding and analyzing the anti-diffusion behavior in complete carbonation zone of MSWI bottom ash-based alkali-activated concrete. (20th October 2018) - Huang, Guodong; Ji, Yongsheng; Zhang, Linglei; Li, Jun; Hou, Zhihui
Highlights: BA displayed a unique anti-diffusion behavior under natural conditions. The anti-diffusion behavior was influenced by amount of sodium silicate used. Anti-diffusion effect of BA significantly reinforced its carbonation resistance. Abstract: This study investigated the carbonation resistance of municipal solid waste incinerator (MSWI) bottom ash alkali-activated concrete (BA) and Portland cement concrete (CC) through the accelerated carbonation test. The results show that BA has lower resistance against carbonation compared to CC under the conditions of the accelerated carbonation experiment. However, BA displayed a unique anti-diffusion behavior under natural conditions which significantly reinforced its carbonation resistance. The anti-diffusion behavior was closely related to the amount of liquid sodium silicate in the activator. Moreover, the pH value in complete carbonation zone of BA was much higher compared to that of CC. The main reason is that liquid sodium silicate turned into magadiite in BA and then the magadiite turned back to liquid sodium silicate to release a large amount of OH − under low concentrations of CO2 . This resulted in a rapid increase in pH value of the pore fluid and generation of the anti-diffusion behavior.